Cyber Science Education within STEM - Spencer, Angela (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Cyber science education is an essential component within the larger realm of STEM, which encompasses science, technology, engineering, and mathematics. In order to effectively educate and prepare students for future careers in the rapidly-evolving field of technology and digital communication, it is necessary to utilize both quantitative and qualitative research methods. The theoretical framework of constructivism allows educators to actively engage students in hands-on learning experiences that foster critical thinking skills and problem-solving abilities. The importance of cyber science education is evident in the 21 individuals who were interviewed and partcipated for this research study. These participants included educators, administrators, researchers, and industry professionals who all emphasized the need for a strong foundation in cyber science education in order to remain competitive in today's global job market. It is clear that cyber science education is crucial for preparing students for the future workforce and promoting innovation and advancement in various industries.